Debunking Phallacies - Gaines, Michael B (East Carolina University)
The body of work uses photography to explore my personal myth that to be seen as legitimate and successful I need to adhere to socially determined, heteronormative concepts of masculinity and gender binaries. As members of the LGBTQ community continue to discover and redefine our personal identities, declarations of these strict gender binaries and specifically gendered clothing, combined with open discrimination disguised as freedom of speech, violence committed under the auspices of religious freedom, and dubious claims of persecution pervade the rhetoric of the opposition and help to perpetuate this myth. These attacks are a means of intimidation and forcing members of the queer community, myself included, back into the closet and eradicating both our imprint on and presence in society. After years of being told we are less than and don't belong, we instinctively suppress our true identities and deploy increased levels of masking and code-switching - alternating or adjusting our language, grammatical structure, behavior, and appearance to fit into the dominant culture - as a means of self-preservation, and self-sabotage. In researching the work of contemporary and historical photographers who work with identity and LGBTQ-related topics, this series examines these concepts through the lens of photography.
Keywords: lgbtq; personal myth; gender; masculinity; Sex role--Art; Gender identity--Art; Discrimination--Art; Belonging (Social psychology)--Art; Photography; Sexual minorities--Art; Sexual minorities--Identity